2009
DOI: 10.1007/s11232-009-0040-4
|View full text |Cite
|
Sign up to set email alerts
|

Borel resummation of the ɛ-expansion of the dynamical exponent z in model a of the ϕ 4(O(n)) theory

Abstract: We perform the Borel resummation of the currently known terms of the ε-expansion up to order ε 4 of the dynamical exponent z in the critical-behavior model A. We obtain the large-order asymptotic approximation of the ε-expansion of the dynamical exponent and find a significant discrepancy between the currently calculated orders of the expansion and the obtained asymptotic values. We discuss the influence of this deviation on the accuracy of the resummation results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…To make results more reliable one needs to incorporate into the reconstructed series all the information we know about it [13]. For example, for the ϕ 4 model (and some other models) we know high order asymptotics (HOA) for A n [8]:…”
Section: General Considerationsmentioning
confidence: 99%
“…To make results more reliable one needs to incorporate into the reconstructed series all the information we know about it [13]. For example, for the ϕ 4 model (and some other models) we know high order asymptotics (HOA) for A n [8]:…”
Section: General Considerationsmentioning
confidence: 99%
“…For the critical dynamical exponent of the 2D φ 4 -model, z ≈ 2 was mentioned in Ref. [16], and the -expansion method has shown that z c ∈ (2.04, 2.14) [17]. Further, z c has been measured using the heat bath algorithm, yielding z c = 1.9 ± 0.21 [18].…”
Section: Introductionmentioning
confidence: 97%
“…This makes it useless for problems in QFT [4,10] or many-body perturbation theory in condensed matter physics [14] where ≲10 orders are available at best. In such cases the Borel-Padé (BP) technique can be used together with a conformal transformation in the Borel plane [1,10,[30][31][32][33][34][35][36][37]]. …”
Section: Introductionmentioning
confidence: 99%